School Bullies' Intention to Change Behavior Following Teacher Interventions: Effects of Empathy Arousal, Condemning of Bullying, and Blaming of the Perpetrator - Garandeau CF; Vartio A; Poskiparta Elisa; Salmivalli Christina (SPRINGER/PLENUM PUBLISHERS, 2022)
This study examines how bullies' perceptions of how they were treated by a teacher (or other school personnel) during discussions aimed at putting an end to bullying influenced their intention to change their behavior. After each discussion, which took place as part of the implementation of an anti-bullying program, bullies anonymously reported the extent to which they felt that the teacher aroused their empathy for the victim, condemned their behavior, or blamed them. Half of the schools implementing the program were instructed to handle these discussions in a confrontational way-telling the bully that his behavior is not tolerated-while the other half were instructed to use a non-confronting approach. Schools were randomly assigned to one of the two approaches. A total of 341 cases (188 in primary and 153 in secondary schools) handled in 28 Finnish schools were analyzed. Regression analyses showed that attempts at making bullies feel empathy for the victim and condemning their behavior both increased bullies' intention to stop. Blaming the bully had no significant effect. Bullies' intention to change was the lowest when both empathy-arousal and condemning behavior were low. The effects of empathy arousal were stronger when condemning the behavior was low (and vice versa), suggesting that teachers tackling bullying should make sure to use at least one of these strategies. When choosing not to raise the child's empathy, clear reprobation of the behavior is key.